Instilling Anti-Corruption and Anti-Drug Awareness at Mulia Karya Husada Health Vocational School: Menanamkan Kesadaran Anti Korupsi Dan Anti Narkoba Di SMK Kesehatan Mulia Karya Husada - Khanza Hanaya Chairunisa; Kayus Kayowuan Lewoleba; Syarla Bella Dewi Pramesty; Zellda Nur Syachfitri; Halena Chandra Callista; Khozinatun Masfufah; Nazma Putri Fadila (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2024)
Instilling anti-corruption and anti-drug attitudes is the first step in instilling positive attitudes. This is useful for preventing and overcoming the rampant corruption and drugs that can lead the generation of the Indonesian nation into negative things. Through the counseling or socialization method, this activity includes basic materials on drugs and corruption, including the definition, prevention, impacts, factors that can cause abuse, symptoms, the influence of corruption and drugs on the development of the Indonesian economy, religious perspectives, and instilling attitudes in society, especially the younger generation. The importance of instilling anti-corruption and anti-drug attitudes in the fields of formal and non-formal education can encourage awareness of preventing corruption and drugs. The impact is to create the next generation of Indonesia who have honesty, integrity, high responsibility, and intelligence in leading Indonesia in the future. This can lead to the realization of the golden Indonesia 2045.